The bidirectionality of buying behavior and risk perception: an exploratory study. Issue 5 (20th October 2021) - Zulauf, Katrin; Cechella, F. Schneider; Wagner, R.
ABSTRACT: The coronavirus pandemic has changed retailers' proceedings, consumers' buying behavior, and the perception of space within the aisles. In a grounded theory–building procedure, the study questions the relationships of consumers' perceived risk, adapted behaviors, and emotional self-regulation. Only a few studies have focused on customer behavior in such disruptive situations. They generally take a unidirectional perspective and explain panic buying and stockpiling by considering buying behavior as only a reaction to panic and uncertainty. We conducted 18 qualitative interviews in Brazil and Germany to gain insight into changes in buying behavior and consumers' feelings on the changed circumstances, which provided a bidirectional perspective on perceived risk, adapted buying behavior, and emotional self-regulation. We attempt to explain changed buying behavior as well as differing behaviors and motives in Brazil and Germany during the crisis. Critical reflection on media reports about panic buying and hoarding as well as on self-observed situations in local stores affords a better assessment of the overall situation and risk.